Institutional implications of governance of local common pool resources on livestock water productivity in Ethiopia - Teklewold, T.; Mapedza, Everisto D.; Amede, Tilahun (Cambridge University Press, 2011)
Improving water productivity depends on how local communal water and grazing resources are governed. This involves institutional and organizational issues. In the mixed farming systems of the Amhara Regional State, Ethiopia, non-participatory water users’ associations, neglect of traditional water rights, corruption, village power relations, inequitable allocation of irrigated land and free-grazing practice impact the governance of local common pool resources (CPR). Indigenous governance structures for CPR such as the kire are participatory and effective in terms of rule enforcement. Externally initiated governance structures lack acceptance by farmers and sufficient support from local government. In order to improve water productivity in the mixed farming systems, institutional deficiencies need attention and existing indigenous governance structures require recognition and support.